Elevated novel inflammatory markers in heart failure patients are associated with increased risk of adverse outcomes within one year: insights from a longitudinal study - Zhao, Zeng; Yuan, Chunmei; Lan, Ting; Liu, Feng; Liu, Guobin; He, Yuping; Li, Jing; Liu, Xingjun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundInflammation has been widely recognized as a key contributor to the pathogenesis of numerous diseases, including cardiovascular disorders. This study aims to investigate the associations between different novel inflammatory markers and adverse outcomes within one year in patients with HF, and to identify the most effective predictor.MethodsThree inflammatory markers—Systemic Inflammatory Response Index (SIRI), Systemic Immune-Inflammatory Index (SII), and Neutrophil-to-Lymphocyte Ratio (NLR)—were evaluated. Cox regression analysis was performed to examine their associations with adverse outcomes within one year. Kaplan–Meier (KM) survival analysis was used to estimate the cumulative risk of adverse events. Additionally, receiver operating characteristic (ROC) curves, time-dependent ROC curves, and C statistics were applied to compare the predictive performance of these markers.ResultsAll three inflammatory markers were significantly associated with adverse one-year outcomes in HF patients. For each one standard deviation increase in SIRI, SII, and NLR, the risk of re-hospitalization increased by 45.5%, 54.9%, and 63.7%, respectively, while the risk of death increased by 63.8%, 70.1%, and 92.9%, respectively. ROC analysis indicated that SIRI had superior predictive performance compared with SII and NLR, and time-dependent ROC results further confirmed its stronger prognostic value.ConclusionThis study demonstrate that several novel inflammatory markers are strongly associated with adverse one-year outcomes in HF patients. Comparative analysis revealed that SIRI provides the most robust predictive performance, highlighting its potential as a valuable clinical tool for monitoring and risk stratification in HF management.